An approach to value creation in open data for small and medium-sized enterprises using 'R' ecosystem - Albino, Joao Pedro [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
With the technologies proliferation for Internet, such as cloud computing, mobile devices, social media and the internet of things, small and medium enterprises, despite their smaller size, less revenue and small number of employees cannot operate with less information. There are many opportunities for these organizations however, additional tools are needed to generate potential value from these data. When dealing with value creation it is essential identify the main beneficiaries from value being created. The research's objective, still in development, is to create applications using open technology for information treatment and display to make them more explicit creating value in such open data. To validate the principal research's theoretical concept, this paper conducted a proof of concept with open data from a federal government agency that supports and finances investments in small and medium enterprises. The results proved to be possible to develop predictions about the possible investment expenditures for next year in each sector.
Keywords: Analytics; Big Data; Open Data; R Language; Small and Medium Enterprises